A minimally invasive lab protocol for fibroblasts isolation from 1-mm skin punch biopsies in pediatric patients - María Heredia-Torrejón; Begoña Puga-López; María Dolores Guerrero-López; Raúl Montañez; Alfonso María Lechuga-Sancho (PLoS ONE, 2026)
Skin biopsies provide a valuable source of culturable cells for a broad range of clinical and biomedical research applications. However, conventional methods for establishing primary cell cultures typically require relatively large tissue specimens obtained through invasive procedures that involve intradermal anesthesia, suturing, and subsequent wound care. These factors are of particular concern when working with pediatric populations. To address these limitations, we developed a simplified protocol that reduces patient discomfort by minimizing the punch biopsy diameter to as little as 1 mm. Despite the markedly smaller sample size, this method consistently enables the successful establishment of primary fibroblast cultures, with no complications reported to date. This streamlined approach is compatible with basic cell culture facilities and provides a reliable source of fibroblasts for downstream applications. Overall, this protocol represents a meaningful advancement in both pediatric research and clinical practice.